1982
DOI: 10.1364/ao.21.001146
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of IR laser backscatter spectra from sulfuric acid and ammonium sulfate aerosols

Abstract: An optical system employing a tunable carbon dioxide laser has been used to investigate backscatter signatures of aerosols as a function of wavelength. Submicron sulfuric acid or ammonium sulfate aerosols are produced with a vapor-condensation aerosol generator. The aerosol is contained in a 1-m long windowless aerosol chamber, and laser radiation backscattered from the irradiated aerosol is collected and measured as the laser is tuned from 9.2 to 10.8 microm. The volume backscatter coefficient is calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…98.5 wt% (Gmitro & Vermeulen, 1964). For an acid bath between 95 and 98 wt%, the corresponding vapor is 72-92 wt% acid, with only a small dependence on temperature between 60 and 100 • C (Mudd, Kruger, & Murray, 1982). Particle compositions should therefore lie within this same wt% range, omitting differential loss of the two species to the walls.…”
Section: Acid Content Of the Sulfuric Acid Nanoparticles At Low Relatmentioning
confidence: 99%
“…98.5 wt% (Gmitro & Vermeulen, 1964). For an acid bath between 95 and 98 wt%, the corresponding vapor is 72-92 wt% acid, with only a small dependence on temperature between 60 and 100 • C (Mudd, Kruger, & Murray, 1982). Particle compositions should therefore lie within this same wt% range, omitting differential loss of the two species to the walls.…”
Section: Acid Content Of the Sulfuric Acid Nanoparticles At Low Relatmentioning
confidence: 99%
“…Clearly, what is needed is an in situ technique that can provide information about the structure and water content of the particles. While infrared (IR) spectroscopy of submicron salt particles is not a particularly good probe of morphology, it has been applied quite successfully to studies of the composition of aerosol particles [Anthony et al, 1995;Bertram et al, 1996;Clapp et al, 1995;Cziczo et al, 1997;Mudd et al, 1982; Weis and to the study of the association of water with supported sodium chloride crystals and crystal-lites [Dai et al, 1995;Ewing and Peters, 1997;Foster and Ewing, 1998;Peters and Ewing, 1997a, b]. In a recent IR spectroscopic study of the crystallization and deliquescence of NaC1 aerosol [Cziczo et al, 1997], solid NaC1 aerosol particles were found to retain a measurable amount of H20 down to 4% RH.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been infrared studies of the collected (NH4)2SO 4 particles of aerosols [Johnson and Kumar, 1991 ] and IR backscatter spectra over a narrow spectral range (1090-920 cm -•) [Mudd et al, 1982], we present here extinction spectra of suspended (NH4)2SO 4 particles over a broad spectral range (4000-600 cm-•). We also show spectra of aerosols composed of metastable supersaturated aqueous (NH4)2SO 4 droplets.…”
Section: Introductionmentioning
confidence: 99%